(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Resveratrol, a stilbene phytoalexin, has been gaining importance as an antioxidant with anti-carcinogenic and cardio protective properties. The polyphenol, mainly found in grapes and red wines, has also been characterized from berry fruits and peanuts. However, literature concerning its occurrence in underutilized fruits of India is sparse. With the objective to add value to underutilized fruits with low economic value, resveratrol was quantitated. The study envisages expansion of fruit juice industry in terms of functional fruit juices with several health benefits. In this regard, mulberry (Morus rubra), Indian blackberry or jamun or jambul fruit (Syzygium cumini) and jackfruit (Artocarpus heterophyllus) of Indian origin were explored for processing in terms of resveratrol. Since fermentation brings about quality changes in fruit beverages, studies were focussed to analyze changes in polyphenols, anthocyanins, antioxidant capacity and individual phenolic acids and resveratrol content in fruit wines prepared by fermentation. Wine polyphenols are known to provide protection against atherosclerosis and resveratrol is the main polyphenol responsible for French paradox phenomenon. Nowadays polyphenols are gaining importance in treating metabolic disorders like Type 2 diabetes. This study describes effects of feeding polyphenol rich mulberry and jamun wines to streptozotocin-induced diabetic rats.